2018
DOI: 10.20473/bhsj.v1i1.8208
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Profile, Clinical and Analysis of Osteoarthritis Patients in Surabaya

Abstract: Introduction: Osteoarthritis is a degenerative joint disease which affects joint cartilage. As many as 80% patients movement are limited and 25% of them can not even perform daily activities. Osteoarthritis is one of the ten most disabling diseases in developed countries. Due to its chronic and progressive nature, socio-economic impacts in many developed and developing countries are enormous. The purpose of this study is to determine the profile of patients with osteoarthritis in the Orthopedic Department of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 13 publications
1
11
0
15
Order By: Relevance
“…11 The research conducted at the Internal Medicine Installation and Orthopedic & Traumatology Installation at Dr. Soetomo General Academic Hospital in September -October 2016 also showed similar results which showed that majority of knee osteoarthritis patients were obese. 12 Obesity induces several pathways that predispose an individual to knee osteoarthritis. Obesity causes abnormal joint loads that lead to the change of composition and properties of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…11 The research conducted at the Internal Medicine Installation and Orthopedic & Traumatology Installation at Dr. Soetomo General Academic Hospital in September -October 2016 also showed similar results which showed that majority of knee osteoarthritis patients were obese. 12 Obesity induces several pathways that predispose an individual to knee osteoarthritis. Obesity causes abnormal joint loads that lead to the change of composition and properties of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that there was increased production of protein, nitric oxide and growth factors, which increased neoangiogenesis, tenocyte and fibroblast proliferation, and collagen synthesis, which further increased tissue catabolism, healing and remodeling. (3) Acoustic cavitation is also formed due to the tensile phase of the shock wave. This cavitation effect is the second effect of ESWT, which is also increasing tissue regeneration by increased tissue permeability, and efficiently destroying the calcification deposits of the soft tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, the prevalence of OA that has been diagnosed radiologically reaches 15.5% in men and 12.7% in women aged 40-60 years. (3) Also at the outpatient clinic of the Medical Rehabilitation Department, Cipto Mangunkusumo Hospital, Indonesia, the number of patients with KOA in 2016 reached 1,018 patients (15.2% of the total number of outpatients in the musculoskeletal division). (4) The proportion of people with symptomatic KOA increases with age and their body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…Hasil dari penelitian ini berbeda dengan hasil penelitian yang dilakukan oleh Ahmad dkk di RSUD Dr. Soetomo Surabaya pada bulan September-Oktober tahun 2016 yang mendapatkan bahwa kelompok usia 60-69 tahun (43%) paling sering menderita osteoartritis sendi lutut dan diikuti oleh kelompok usia 50-59 tahun (29%) pada peringkat kedua. 18 Alasan perbedaan hasil antara kedua penelitian ini belum diketahui penyebabnya dan dibutuhkan penelitian lebih lanjut untuk menjawab hal ini. Penelitian yang dilakukan oleh Grace dkk di RSUP Sanglah Bali pada bulan Januari -Juni tahun 2018 menyatakan bahwa kelompok usia 60-69 tahun (41,7%) paling sering menderita osteoartritis dan diikuti oleh kelompok usia 50-59 tahun (26,7%) pada peringkat kedua.…”
Section: Research Articleunclassified